PENINGKATAN KEMAMPUAN SMASH BOLA VOLI MELALUI METODE TARGET GAMES PADA SISWA SMA NEGERI 8 JENEPONTO - BADARU, BENNY; juhanis, juhanis; Zainuddin, M. Said; Sufitriyono, Sufitriyono; suwardi, suwardi; Pratama, Rivan Saghita (UNIVERSITAS NEGERI MAKASSSAR, 2023)
This research is a class action research (classroom action research) which aims to determine the increase in the ability to smash volleyball with the target games method in class XI IPS 2 SMA Negeri 8 Jeneponto. The design of this study uses the Kurt Lewin model in 2 cycles and in each cycle there are 2 meetings consisting of planning, implementation & observation, and reflection. The research subjects were 28 students of class XI IPS 2 at SMA Negeri 8 Jeneponto. The results showed that the ability to smash volleyball with the target games method of students in class XI IPS 2 SMA Negeri 8 Jeneponto experienced an increase, namely from the results of the first cycle test the complete category was 11 students or 39% and the incomplete category was 17 students or 61%. Meanwhile, in cycle II, the results of the completeness of students were obtained, namely the complete category of 26 students or 93%, while the incomplete category in cycle II was 2 students or 7%, so it can be concluded that the results of cycle II increased by 93% from cycle I..